The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1128/mbio.02060-19
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolite Repair Enzyme Phosphoglycolate Phosphatase Regulates Central Carbon Metabolism and Fosmidomycin Sensitivity in Plasmodium falciparum

Abstract: The malaria parasite has a voracious appetite, requiring large amounts of glucose and nutrients for its rapid growth and proliferation inside human red blood cells. The host cell is resource rich, but this is a double-edged sword; nutrient excess can lead to undesirable metabolic reactions and harmful by-products. Here, we demonstrate that the parasite possesses a metabolite repair enzyme (PGP) that suppresses harmful metabolic by-products (via substrate dephosphorylation) and allows the parasite to maintain c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Given that fosmidomycin targets DXR, it is likely that the reduction in DXR’s substrate (DOXP) in PS-3-resistant parasites, coupled with a decrease in MEcPP and IPP, results in an increase in fosmidomycin activity. Increased sensitivity to fosmidomycin has also been reported in P. falciparum parasites lacking phosphoglycolate phosphatase (PGP) ( 40 ). PGP, a third member of the P. falciparum HAD family, has been shown to be involved in regulating glycolysis and PPP flux in asexual P. falciparum ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that fosmidomycin targets DXR, it is likely that the reduction in DXR’s substrate (DOXP) in PS-3-resistant parasites, coupled with a decrease in MEcPP and IPP, results in an increase in fosmidomycin activity. Increased sensitivity to fosmidomycin has also been reported in P. falciparum parasites lacking phosphoglycolate phosphatase (PGP) ( 40 ). PGP, a third member of the P. falciparum HAD family, has been shown to be involved in regulating glycolysis and PPP flux in asexual P. falciparum ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased sensitivity to fosmidomycin has also been reported in P. falciparum parasites lacking phosphoglycolate phosphatase (PGP) ( 40 ). PGP, a third member of the P. falciparum HAD family, has been shown to be involved in regulating glycolysis and PPP flux in asexual P. falciparum ( 40 ). In Δ pgp parasites, the loss of PGP leads to the inhibition of the PPP enzyme 6-phosphogluconate dehydrogenase (6-PGD), resulting in reduced glycolytic flux and causing reduced isoprenoid biosynthesis and increased sensitivity to fosmidomycin ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, standard in vitro inhibitory activity of a candidate compound can be confounded by altered pathogen metabolism due to growth media composition (Hicks et al, 2018; Pethe et al, 2010) and conversely an understanding of these interactions can potentiate treatment (Vestergaard et al, 2017). These complex interactions are best understood in cases of bacterial pathogenesis, but recently, similar trends are apparent in eukaryotic pathogens (Dumont et al, 2019; McLean and Jacobs-Lorena, 2017; Murithi et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…A third, less explored option, is the impact of metabolic and environmental heterogeneity on the efficacy of a given antimicrobial agent (Yang et al, 2017). Factors such as pathogen respiration (Lobritz et al, 2015), ATP levels (Conlon et al, 2016) and buildup of metabolic intermediates (Dumont et al, 2019) as well as environmental stressors such as the host immune response (Rowe et al, 2020) can modulate antibiotic efficacy. Recent work has shown that when the metabolic state and growth rate of microbes are disentangled, the factor that correlates with antibiotic efficacy is the microbial metabolic state (Lopatkin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%